Eksistensi dan Dinamika Kosa Kata Bahasa Jawa Kuna pada Masyarakat Bali Masa Kini - Ni Ketut Ratna Erawati (Universitas Udayana, 2015)
Historically, Bali had experienced two processes, namely“Javanisation” on the one side and “Balinisation” on theother side. The melting process of them can implicate for thedevelopment of culture and Balinese language. Acculturationand language may not be inevitable. The phenomenon canbe proven through a number of Old Javanese linguisticdata used by Balinese people. Based on the data obtainedturned out to use the vocabulary Old Javanese still existby following system or Balinese rules. It can be seen in thewritten realm and verbal realm. In the written realm, the useof Old Javanese often found in literary works, inscriptions(chronicle), awig-awig (traditional law), the person’s name,the name of the area or place, and name of organization orsocial group. In the verbal realm, the Old Javanese usage canbe encountered in activities, such as performing arts, customsand religious ceremonies, mabebasan (textual singing),advice, Balinese language speech contest or in seminars. Theuses of Old Javanese vocabulary in the realm of languagegive the impression of authority, more archaic, and moreaesthetically pleasing.